Carta de Roberto H. Todd a Charles R. Hartzell - Todd, Roberto H.; Hartzell, Charles R. (My University, 1934)
Acuso de recibo por la cantidad enviada para ayudar a la viuda e hijos de Manuel Angel Martínez Dávila
Keywords: Martínez Dávila, Manuel A.,1883-1934